Lung function in African infants: A pilot study. Issue 1 (11th December 2013) - Gray, D.M.; Willemse, L.; Alberts, A.; Simpson, S.; Sly, P.D.; Hall, G.L.; Zar, H.J.
Summary Background The burden of childhood respiratory illness is large in low and middle income countries (LMICs). Infant lung function (ILF) testing may provide useful information about lung growth and susceptibility to respiratory disease. However, ILF has not been widely available in LMICs settings where the greatest burden of childhood respiratory disease occurs. Aim To implement and evaluate a pilot study of ILF testing in a semi‐rural setting in South Africa. Method Infant lung function testing was established at a community hospital in South Africa. All measures were done in unsedated infants during sleep. Measurements, made with the infant quietly breathing through a face mask and bacterial filter, included tidal breathing (TBFVL), exhaled nitric oxide (eNO), and sulphur hexafluoride multiple breath washout (MBW) measures using an ultrasonic flow meter and chemoluminescent NO analyzer. Results Twenty infants, mean age of 7.7 (SD 2.9) weeks were tested; 8 (40%) were Black African and 12 (60%) were mixed race. Five (25%) infants were preterm. There were 19 (95%) successful TBFVL and NO tests and 18 (90%) successful MBW tests. The mean tidal volume was 30.5 ml (SD 5.9), respiratory rate 50.2 breaths per minute (SD 8.7), and eNO 10.4 ppb (SD 7.3). The mean MBW measures were: functional residual capacity 71 ml (SD 13) and the lung clearance index 7.6 (SD 0.5). The intra‐subject coefficient of variations (CV) of lung function measures were similar to published normative data for Caucasian European infants. Conclusion In this study we demonstrate that unsedated infant lung function measures of tidal breathing, MBW, and eNO are feasible in a semi‐rural African setting with rates comparable to those reported from high income countries. Pediatr Pulmonol. 2015; 50:49–54. © 2013 The Authors. Pediatric Pulmonology published by Wiley Periodicals, Inc.